(3ebGdI aj GdHMhK GdCQHYI GdYdejI Yf UfGYI GdefWbs - (3CHh RcQjG jMji Hf YOj Hf RcQjG GdajdSha GdfUQGfj GdjYbhHjs
(3ChdgG (B:s
(3bGd dh hGabJ CaYGd LejY GdHTQ CbhGdge ai EKHGJ GdMb hGdEfbjGO dg dCZfGfG Pdc Yf Jcda EjGfI aVd GdVGYI GdefWbjI s
(3BNQgG (B:s
(3heJi cGfJ ehGOgG NHjKI cGfJ cGdfGQ GdeTJYdI ai GdYhO efgi GdebGdI GdSeGLjI ai SjGSI GdfaS hGddg Gdehab s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(4818) s
Keywords: (3GdeLGejYs